DMFT index assessment and microbiological analysis of Streptococcus mutans in institutionalized patients with special needs - Tanaka, Marcia H. [UNESP]; Bocardi, Karina [UNESP]; Kishimoto, Kátia Yukari [UNESP]; Jacques, Paula; Spolidório, Denise Madalena Palomari [UNESP]; Giro, Elisa Maria Aparecida [UNESP] (My University, 2009)
Aim: To assess the DMFT (D = decayed; M = missing; F = filled) index of institutionalized patients with mild and moderate physical and mental disabilities and to correlate it with the Streptococcus mutans (S. mutans) counts in the supragingival bacterial biofilm. Methods: Dental examination of 28 patients aged 15 to 25 years was conducted to determine the DMFT index (number of decayed, missing and filled teeth). Supragingival plaque samples were collected from the buccal surfaces of all teeth. The samples were inoculated in SB20 medium and incubated at 37 °C for 48 hours. Spearman's correlation test was applied (p = 0.05) to evaluate the correlation between the DMFT index and the amount of S. mutans. Results: The mean DMFT recorded was 7.68 and a large mean number of S. mutans colony-forming units (cfu > 10 6) was found. No statistically significant correlation was found between the DMFT index and the number of S. mutans. Conclusions: Under the conditions of this study, no correlation was found between the DMFT index and the number of S. mutans cfu in institutionalized patients with mental retardation and physical disabilities.
Keywords: Dental caries; Disabled persons; Streptococcus mutans